Direct synthesis of mesoporous molecular sieves of Ni-SBA-16 by internal pH adjustment method and its performance for adsorption of toxic Brilliant Green dye - Asma Tufail Shah; Muhammad Imran Din; Farva Nausheen Kanwal; Muhammad Latif Mirza (Arabian Journal of Chemistry, 2015)
An ordered mesoporous novel material Ni-SBA-16 has been synthesized by internal pH-adjustment method. The synthesized material has been characterized by small angle XRD (SXRD), wide angle XRD (WXRD), Scanning Electron Microscope (SEM), High-Resolution Transmission Electron Microscope (HRTEM), Fourier-transform Infra-red (FTIR) spectroscope and Nitrogen Adsorption desorption techniques. The characterization results have shown that material possesses highly ordered mesostructure with high surface area (736 m2/g) and large pore diameter (3.8 nm). FTIR and WXRD spectra revealed that nickel was uniformly dispersed on SBA-16 surface. The synthesized material has been used as adsorbent for removal of toxic Brilliant Green dye due to its large surface area and pore size. At optimized conditions, almost 100% of Brilliant Green dye was removed from aqueous solution by Ni-SBA-16. The isotherms analysis indicates that the Langmuir and Hill models provide the best correlation of the experimental data. The maximum adsorption capacity (qmax) of Ni-SBA-16 for Brilliant Green dye was 322.58 mg/g.